Data and Metadata Brokering – Theory and Practice from the BCube Project. (12th January 2017) - Khalsa, Siri Jodha Singh
EarthCube is a U.S. National Science Foundation initiative that aims to create a cyberinfrastructure (CI) for all the geosciences. An initial set of "building blocks" was funded to develop potential components of that CI. The Brokering Building Block (BCube) created a brokering framework to demonstrate cross-disciplinary data access based on a set of use cases developed by scientists from the domains of hydrology, oceanography, polar science and climate/weather. While some successes were achieved, considerable challenges were encountered. We present a synopsis of the processes and outcomes of the BCube experiment.